Welfare, physiological stress responses, and carcass and meat quality in goats subjected to different slaughter methods - Sabow, Azad Behnan (2016)
There is increasing global demand for halal meat. However, halal slaughter is controversial with respect to animal welfare. Therefore, harmonizing spiritual views, animal welfare, slaughter methods and meat quality is a continued research effort. The current study aims to describe two experiments that link physiological stress responses following different methods of slaughter to carcass and meat quality using goats as a model. In the first experiment, blood biochemistry, electroencephalographic changes and meat quality characteristics associated with possible noxious stimuli following neck cut of goats subjected to conscious halal slaughter and slaughter following minimal anesthesia were assessed in order to validate the minimal anesthesia technique. Ten male Boer crossbred goats were divided into two groups of 5 animals each and subjected to either halal slaughter without stunning (HS) or slaughter following minimal anesthesia (AS) using 5mg/kg propofol administered through cephalic vein and maintained with halothane in 100% oxygen. Blood analysis revealed that the intensity of response for most biochemical blood parameters, except glucose and lactate was not affected by slaughter method. Based on the EEG results, the changes in brain electrical activities were not significantly different between anesthetized and non-anesthetized animals. The HS goats had earlier (p<0.05) cessation of heart beats compared with AS goats. Blood loss at exsanguination, residual hemoglobin and myoglobin in meat were not different between HS and AS. At pre-rigor, HS had lower (p<0.05) muscle pH and glycogen compared to AS. HS meat had lower (p<0.05) drip loss than AS throughout ageing. After 24 h postmortem, AS meat had higher population of lactic acid bacteria than HS group. The present results demonstrate that the noxious stimulus from neck cut is present in both conscious and minimally anaesthetized goats. Slaughtering goats following minimal anesthesia did not affect bleeding efficiency and meat quality in comparison with slaughtering goats fully conscious. The second experiment compared different methods of pre-slaughter electrical stunning and slaughter without stunning on physiological stress responses, carcass and meat quality in goats. Thirty-two crossbred Boer bucks were divided into four groups of 8 animals and subjected to halal slaughter without stunning (SWS), low frequency head-only electrical stunning (LFHO; 1 A for 3 s at 50 Hz), low frequency head-to-back electrical stunning (LFHB; 1 A for 3 s at 50 Hz) and high frequency head-to-back electrical stunning (HFHB; 1 A for 3 s at 850 Hz). Slaughtering of animals with or without stunning was performed under minimal anesthesia. Analysis of the sticking blood revealed that all variables were significantly (p<0.05) higher than their values in blood samples taken in the farm, lairage, after the point of anesthesia induction and prior to stunning/slaughter. Following slaughter, the SWS animals had higher changes of electrical activity of the brain (EEG) than that of pre-slaughter while electrical stunning maximized the possibility of post stunning insensibility. Based on EEG data, the LFHO animals had the highest changes of electrical activity of the brain at stunning point compared to other stunned animals. LFHB induced a cardiac arrest in all the goats contrary to LFHO and HFHB. The duration between the point of cut and producing cardiac fibrillation for the HFHB goats was similar to that of LFHO and SWS groups. At 12 h postmortem, LFHO, LFHB and HFHB exhibited lower (p<0.05) glycogen and pH and higher lactate and glycolytic potential values and faster pH decline than SWS. The pH, glycogen, lactate, glycolytic potential, drip loss, color, shear force, sarcomere length and myofibrillar fragmentation index at 1, 7 and 14 d postmortem did not differ between treatments. The LFHO, LFHB and HFHB exhibited higher (p<0.05) cooking loss than SWS at 7 and 14 d postmortem. Incidences of speckles and blood splash were higher (p<0.05) in electrical stunned goats compared with SWS goats. Nonetheless, HFHB had lower (p<0.05) speckles and blood splash than LFHB and LFHO. The SWS, LFHO and HFHB goats had higher (p<0.05) blood loss and lower residual hemoglobin in muscle compared to LFHB. The LFHB meat had higher (p<0.05) TBARS value and bacterial counts at m7 and 14 d postmortem than other treatments. Immunoblot analysis, carbonyl and thiol content determination revealed that protein oxidation increased with aging time, but was not affected by slaughter methods. The expression of myosin heavy chain and troponin-T reduced while actin remained stable over storage. The present findings indicate that all slaughter methods caused substantial physiological stress responses which may not necessarily translate into compromising of animal welfare and meat quality, as all blood biochemical parameters level observed fell within the normal physiological range for goats. Moreover, HFHB can be used as a substitute for conventional electrical stunning techniques since it meets both the Islamic requirement of the animal being alive at the moment of slaughter and animal welfare requirement of insensibility during exsanguination.